THE FUNCTION OF ALLUSION IN MODERNIST POETRY - Kalbayev Abdulaziz Shavkatovich; Abduramanova Diana Valerevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article explores the function of allusion in modernist poetry, a key literary technique employed by poets to enrich meaning, critique societal norms, and engage with literary traditions. Allusion, as a reference to historical, cultural, or literary texts, is not merely decorative in modernist works but serves as a vital tool for addressing themes of fragmentation, disillusionment, and existential crisis. Through a close examination of poets such as T.S. Eliot, Ezra Pound, W.B. Yeats, and others, the essay demonstrates how allusion deepens thematic exploration by tapping into shared cultural knowledge, while also fostering intertextual connections that both challenge and transform prior literary traditions. Furthermore, allusion in modernist poetry functions as a powerful vehicle for social critique, juxtaposing contemporary realities with past ideals to reveal the disjunction between the two.